Anesthetic Challenges for Modified Bentall Procedure in a Pregnant Marfan Patient with Acute Stanford Type A Dissection - Irma Tantri; Theresa Menor; Nelia Laborte (Fakultas Kedokteran Universitas Pelita Harapan, 2019)
Aortic dissection is a life-threatening condition which requires immediate surgical intervention. It has been estimated that half of aortic dissection and/or ruptures in women younger than 40 years of age have been associated with pregnancy.19 The limited data on the coincidence of Marfan syndrome, pregnancy and aortic dissection makes its anesthetic management a formidable challenge to any anesthesiologist.This is a case of a 33-year-old G1P0, 28 weeks age of gestation with Marfan syndrome, who had Aortic Dissection Stanford type A and underwent an emergency Modified Bentall’s surgery with cardiopulmonary bypass and deep hypothermic circulatory arrest.This case illustrates the dilemma of managing this case since there are two patients involved, mother and fetus. Wrong decision could result in demise of both. Although the aim is life for both, survival of one without neurologic sequelae is already considered a success.